2021
DOI: 10.1186/s12887-021-02759-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of respiratory viruses in 4403 pediatric patients from multiple hospitals in Guangdong, China

Abstract: Background Acute respiratory infections (ARI) cause considerable morbidity and mortality worldwide, especially in children. Unfortunately, there are limited multi-center data on common viral respiratory infections in south China. Methods A total of 4403 nasal swabs were collected from children in 10 cities in Guangdong, China in 2019. Seven respiratory viruses, influenza A virus (IFA), influenza B virus (IFB), respiratory syncytial virus (RSV), ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 30 publications
4
10
1
Order By: Relevance
“…RSV and IFA were most frequently detected during 2017-2021. These ndings are consistent with previous reports from China [34,37]. Detection rate of AdV was third highest in this study.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…RSV and IFA were most frequently detected during 2017-2021. These ndings are consistent with previous reports from China [34,37]. Detection rate of AdV was third highest in this study.…”
Section: Discussionsupporting
confidence: 94%
“…Between 2003-2008, GA2 was the predominant genotype in China which was replaced by NA1 genotype from 2008-2013 [9,26,48]. During this study, we found ON1 as predominant genotype con rming rapid spread of this genotype This nding is consistent with recent studies in China, reporting dominance of ON1 genotype [9,15,19,[24][25][26]34]. To date, ON1 genotype has been detected in 21 countries indicating widespread dissemination of this genotype.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Indication for sampling can be respiratory infection (respiratory panel) or SARS-CoV-2 screening (isolated SARS-CoV-2 PCR). The epidemiology and etiology of respiratory infections in this well-defined age category have been described in detail by the scientific community and were therefore selected ( 11 , 13 , 31 , 36 ). Ethical approval has been granted by the Educational-Support Committee of the Research Ethics Committee UZ/KU Leuven and the data was pseudonymized prior to analysis.…”
Section: Methodsmentioning
confidence: 99%